2011
DOI: 10.1007/s11250-011-9841-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body condition score at mating on the reproductive performance of Kivircik sheep under an extensive production system

Abstract: The aim of this study was to determine the effects of the body condition score (BCS) of ewes before and during the mating season on their reproductive performance under an extensive production system. In this study, 240 Kivircik sheep from the flocks of two breeders were used for over a 2-year period. The flocks were fed under extensive conditions on natural pastures throughout the year. The ewes were synchronized in two different periods, one of which was 45 days before the other. Before the introduction of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 12 publications
(12 reference statements)
3
27
0
1
Order By: Relevance
“…Gender had a statistically significant effect on muscle depth. These results are consistent with literature data [3,17] .…”
Section: Discussionsupporting
confidence: 94%
“…Gender had a statistically significant effect on muscle depth. These results are consistent with literature data [3,17] .…”
Section: Discussionsupporting
confidence: 94%
“…The differences between the body conditions scores of ewes in this study could be attributed to their status within the hierarchy of the herd, competition among them and physiological differences (milk yield levels, suckling and having twin lamb) (Gonzáles-García et al, 2015). A BCS above 2.5 is recommended at mating (Thompson and Meyer, 1994;Yilmaz et al, 2011;Vatankhah et al, 2012;Van-Burgel et al, 2011). The BCS values of ewes determined in the present study are in accordance with this recommendation (68.2 % of ewes were in the medium and fat BCS groups; Table 2 and Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, there are many reports that ovulation rate and litter size were influenced by ewe BW, parity and BCS (Michels et al, 2000). It was reported in some studies (Michels et al, 2000;Yilmaz et al, 2011;González-García and Hazard, 2016) that parity has a strong effect on fecundity and prolificacy or litter size in sheep farming. The present study showed that animal body fat reserves can affect the return rate and fecundity of ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported direct impacts of ewe BCS on reproductive performance (Yılmaz et al, 2011), colostrum production (Jalilian and Moeini, 2013), survival and growth rates of lambs (Sarı et al, 2013;Corner-Thomas et al, 2015a, b).…”
Section: Introductionmentioning
confidence: 99%